Non-Hermitian route to higher-order topology in an acoustic crystal - He Gao (Nature Portfolio, 2021)
Losses, due to their non-Hermitian nature, are generally disregarded or even considered harmful when looking for non-trivial topological phases. Here, the authors experimentally demonstrate that higher-order topology can emerge as a result of introducing losses in an acoustic crystal.